ANALISIS YURIDIS PEMBENTUKAN PENGADILAN MARITIM DI INDONESIA SEBAGAI BENTUK MANAJEMEN PERTAHANAN KEDAULATAN WILAYAH LAUT NKRI - Mohamad Firdaus; Anak Agung Monny Aryadi Djlantik; Asgar Hasrat Sjarfi (CV. Denasya Smart Publisher, 2026)
As the world's largest archipelagic nation, Indonesia possesses vast and strategic maritime territory, both economically and geopolitically, and for national defense. However, Indonesia currently lacks a maritime court specifically addressing maritime disputes and violations. Maritime case management remains scattered across various judicial bodies, leading to fragmented authority and weak maritime law enforcement. This study aims to legally analyze the urgency of establishing a maritime court in Indonesia as a defense management instrument to safeguard the maritime sovereignty of the Unitary State of the Republic of Indonesia (NKRI). The research method used is normative juridical, with legislative, conceptual, and comparative approaches. The results indicate that the establishment of a maritime court is a strategic national necessity to strengthen maritime law enforcement, increase legal certainty, and support a national defense system based on maritime sovereignty